2019
DOI: 10.1111/cyt.12732
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminate thyroid nodules (TIR3A/TIR3B) according to the new Italian reporting system for thyroid cytology: A cytomorphological study

Abstract: Objective: The Italian reporting system for thyroid cytology classifies indeterminate lesions as TIR3A (low risk) or TIR3B (high risk) and is meant to provide practical guidance rather than a detailed consideration of morphological features. We aimed to assess which cytological features have the most diagnostic value and whether they are effective in classifying nodules as either TIR3A or TIR3B and in predicting histological outcomes.Methods: Thyroid fine-needle aspirates from 111 indeterminate nodules were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…We compared the data of our study with the results of similar studies on Italian adult cohorts and the main studies on pediatric cohorts based on the BSRTC classification (Table 5) [32][33][34][35][36][37][38][39][40][41][42][43][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. Italian studies based on the 2014 SIAPEC classification report an average malignancy rate of 14.2% for TIR3a nodules and 44.7% for the TIR3b cytological category in studies with adult cohorts [32][33][34][35][36][37][38][39][40][41][42][43]. In our cohort, we did not observe any malignancy among TIR3a nodules but the amount of histological data was very small, although the follow-up of 4.6 years confirmed the cytological category in all subjects who performed clinical follow-up with FNAB repeated every 12-18 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared the data of our study with the results of similar studies on Italian adult cohorts and the main studies on pediatric cohorts based on the BSRTC classification (Table 5) [32][33][34][35][36][37][38][39][40][41][42][43][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. Italian studies based on the 2014 SIAPEC classification report an average malignancy rate of 14.2% for TIR3a nodules and 44.7% for the TIR3b cytological category in studies with adult cohorts [32][33][34][35][36][37][38][39][40][41][42][43]. In our cohort, we did not observe any malignancy among TIR3a nodules but the amount of histological data was very small, although the follow-up of 4.6 years confirmed the cytological category in all subjects who performed clinical follow-up with FNAB repeated every 12-18 months.…”
Section: Discussionmentioning
confidence: 99%
“…For the adult population, some Italian authors have studied national cohorts affected by thyroid nodules and reported significantly higher sensitivity of the Italian system than the Bethesda one, validating the TIR3a/TIR3b subclassification for the individuation of benign nodules and malignant tumors, with a ROM of 4-20.8% and 28-60.3%, respectively [32][33][34][35][36][37][38][39][40][41][42][43]. Pediatric studies based on the BSRTC system indicate a higher ROM for indeterminate nodules (39.5% for AUS/FLUS category [44] and 41.5% for the SFN category) compared to adults (30.5 and 28.9% respectively), with no substantial differences in ROM between the two indeterminate categories in both pediatric and adult age [45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…We compared the data of our study with the results of similar studies on Italian adult cohorts and the main studies on pediatric cohorts based on the BSRTC classi cation (Table 5) [33][34][35][36][37][38][39][40][41][42][43][44][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Italian studies based on the 2014 SIAPEC classi cation report an average malignancy rate of 14.2 % for TIR3a nodules and 44.7% for the TIR3b cytological category in studies with adult cohorts [33][34][35][36][37][38][39][40][41][42][43][44]. In our cohort we did not observe any malignancy among TIR3a nodules but the amount of histological data was very small, although the follow-up of 4.6 years con rmed the cytological category in all subjects who performed clinical follow-up with FNAB repeated every 12-18 months.…”
Section: Discussionmentioning
confidence: 99%
“…For the adult population, some Italian Authors have studied national cohorts affected by thyroid nodules and reported signi cantly higher sensitivity of the Italian system than the Bethesda one, validating the TIRa/TIR3b subclassi cation for the individuation of benign nodules and malignant tumors, with a rate of malignancy of 4-20.8% and 28-60.3%, respectively [33][34][35][36][37][38][39][40][41][42][43][44]. Pediatric studies based on the BSRTC system indicate a higher ROM for indeterminate nodules (39.5% for AUS/FLUS category and 41.5% for the SFN category) compared to adults (30.5% and 28.9% respectively), with no substantial differences in ROM between the two indeterminate categories in both pediatric and adult age [46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, at present, the clinical management of thyroid nodules with indeterminate cytology still represents an unresolved issue. Despite the well-known role of clinical aspects on the decision making for patients with indeterminate cytology, the possible influence of specific clinical features on the cytological findings and hence on the indeterminate cytological reports has not been fully investigated so far (6,7). Unfortunately, to date, there is no pre-operative gold standard for accurately predicting the risk of malignancy of a cytologically indeterminate nodule (6,7,8,9,10).…”
Section: Introductionmentioning
confidence: 99%